Students' Knowledge, Attitude, and Behavior Towards Flood Preparedness: A Case Study at a Junior High School in Bekasi, Indonesia - Sumarno, Sumarno; Setiadi, Hafid (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Preparedness in dealing with the coming of floods is very important for the community because, with preparedness, the community can prepare themselves and do first aid after a disaster. knowledge, attitude, and behavior are factors that influence preparedness. This study aims to determine knowledge, attitude, and behavior about flood preparedness at a junior high school in Bekasi, Indonesia. This research method uses quantitative method. Based on data processing and analysis of research conducted regarding the influence of knowledge, attitude, and behavior about flood disaster preparedness in a junior high school in Bekasi, it is concluded that the disaster actions of junior high school in Bekasi positively influence flood disaster preparedness. In this study, it was also found that the variables of knowledge, attitudes, and actions together influence 9% of flood preparedness, while other factors influence the rest.